Cooling, CO2 reduction, and energy-saving benefits of a green-living wall in an actual workplace. (15th May 2023) - Yungstein, Yehuda; Helman, David
Abstract: Vertical green-living walls (VGWs) are a promising solution for sustainable building design. However, their effectiveness in improving indoor air quality and reducing energy consumption in real-world settings still needs to be studied. Here we aim to contribute to this understanding by examining six indoor plant species ( Peperomia obtusifolia, Tradescantia spathacea, Chlorophytum comosum, Spathiphyllum wallisii, Aeschynanthus radicans, and Philodendron hederaceum ) in a 15 m 2 Patrick Blanc's VGW system established in a shared office space ( ∼ 140 m 3 volume). Carbon dioxide (CO2 ) assimilation, transpiration, and stomatal conductance were measured under varying light conditions and CO2 levels. In addition, numerous sensors were placed in the room to assess impacts on the indoor environment. Results indicate that all species but one ( Philodendron ) were equally effective in reducing CO2 . Tradescantia had the highest cooling effect via transpiration. All species except Tradescantia had a very low light compensation point (<5 μmol m −2 s −1 PPFD), indicating their efficiency at reducing CO2 levels even under low light conditions. The net cooling effect of the VGW was 2.5°C–4.5 °C when the ventilation system was on and 1.2°C–3.6 °C when it was off. There was also a positive effect on indoor air quality, with an average CO2 reduction of 5% and sometimes up to 50%. By conducting controlled CO2 enrichment experiments, we estimated a 20% energy consumption savings from reduced air ventilation, equivalent to 1400 kWh/year. These results suggest that VGWs can improve indoor environments and thermal comfort in workplace settings and highlight the importance of choosing appropriate plant species. Highlights: Vertical green-living walls (VGWs) can improve indoor air quality and reduce energy use. We studied six plant species in a hydroponic VGW system in a shared office space. Chlorophytum and Spathiphyllum were the most effective in cooling and reducing CO2 . The VGW had a net 3 ° C-5 ° C cooling effect and CO2 reduction of 5%–50% in the room. The VGW was estimated to save 20% energy consumption, equivalent to 1400 kWh/year.